A PROMISING APPROACH TO ENHANCE SOLUBILITY AND BIOAVAILABILITY BY SELF EMULSIFYING DRUG DELIVERY SYSTEM: A BRIEF REVIEW - Baratam, Srinivasa Rao; Padavala, Veerabhadhra Swamy; Jayanthi, Vijaya Ratna (Innoriginal: International Journal of Sciences, 2018)
Objective: The formulation of self-emulsifying drug delivery system of drugs is to enhance the solubility and bioavailability. More than 40% of available drugs exhibit poor water solubility, resulting in unsatisfactory oral drug delivery.Increasing the bioavailability of drugs is one of the challenges in oral formulations. SEDDS is one of the formulation design to improve the absorption process.SEDDS are the mixture of oil, surfactants and cosolvent/co-surfactants. After administration, the drug remains entrapped/solubilized in the oil phase of the emulsion that is formed in the gastrointestinal tract upon self-emulsification lead to increased solubilization and absorption resulting in increased bioavailability. Conclusion: The review focuses on SEDDS formulating design and characterization along with the technique by which the bioavailability can be improved.